2021
DOI: 10.1111/sjop.12706
|View full text |Cite
|
Sign up to set email alerts
|

Memory complaints and cognitive performance in fibromyalgia and chronic pain: The key role of depression

Abstract: To explore the relationship between perceived cognitive problems and cognitive performance in three different samples, taking into account the possible influence of depression, catastrophizing, pain intensity, or medication. Seventy individuals with fibromyalgia, 74 with non‐malignant chronic pain and 40 pain‐free controls, completed measures of verbal episodic memory, sustained attention, response inhibition, depression, catastrophizing, and pain intensity. Fibromyalgia and chronic pain patients performed wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
1
9
0
2
Order By: Relevance
“…Although at first glance the lack of differences in verbal memory between FM and healthy participants may seem striking, the literature on this matter is in fact inconsistent. Indeed, and in accordance with the present findings, Castel et al [ 30 , 76 ] did not find differences in verbal memory (as measured by the TAVEC) between FM patients and controls. These discrepant results may be explained in part by differences in the dependent variables (i.e., TAVEC conditions) selected to index verbal memory performance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although at first glance the lack of differences in verbal memory between FM and healthy participants may seem striking, the literature on this matter is in fact inconsistent. Indeed, and in accordance with the present findings, Castel et al [ 30 , 76 ] did not find differences in verbal memory (as measured by the TAVEC) between FM patients and controls. These discrepant results may be explained in part by differences in the dependent variables (i.e., TAVEC conditions) selected to index verbal memory performance.…”
Section: Discussionsupporting
confidence: 93%
“…It is also important to mention that, in the present study, the effect of BMI was controlled for in the group comparisons, and that BMI significantly affected verbal memory performance (see below a further discussion of this issue). In conclusion, not all studies have demonstrated differences in verbal memory between FM and healthy participants (e.g., [ 27 , 30 , 32 , 76 ] for negative results). More research is needed to shed light on the verbal memory performance of FM patients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Dieser Unterschied zeigte sich im Vergleich zu Menschen mit neuropathischen Schmerzen und zu gemischten Schmerzen und blieb trotz Berücksichtigung von komorbiden affektiven und Angstsymptomen bestehen [ 97 ]. Menschen mit Fibromyalgie klagen auch stärker über Gedächtnisstörungen und depressive Symptome als Menschen mit anderen chronischen Schmerzformen [ 24 , 87 , 104 ]. Bei generalisiertem und neuropathischem Schmerz wird ein größerer Effekt auf die Kognition angenommen als bei lokalem Schmerz [ 64 ].…”
Section: Chronisches Schmerzsyndrom Und Kognitionunclassified
“…Emotional experience mainly refers to the negative emotions caused by pain, such as anxiety, fear, and anger, which can lead to the ACC activation (Banik et al, 2010; Wiech & Tracey, 2009; Zheng et al, 2018). Numerous studies have shown that pain can impair some cognitive functions, such as the speed of individual information processing, working memory, and executive function (Castel et al, 2021; Lee et al, 2010; Verdejo-García et al, 2009). This impairment effect might be due to the common brain regions involved in psychological pain and cognitive functions.…”
mentioning
confidence: 99%